2022
DOI: 10.3390/foods11040540
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Catfish (Ictalurus punctatus) Bone Powder on Consumers’ Liking, Emotions, and Purchase Intent of Fried Catfish Strips

Abstract: Catfish are the predominant U.S. aquacultural product. However, byproducts from filleting, including bones that are high in calcium, typically go to waste or are sold as a low-valued feed. This research evaluated the potential use of catfish bone powder (CBP; 21.07% calcium) as a food ingredient. Catfish fillet strips were dredged with a breading mix (CBPM) containing 0% (0CBPM), 10% (10CBPM), and 20% (20CBPM) CBP before frying. Consumers (N = 211) evaluated sensory liking (nine-point hedonic scale) and attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 40 publications
(80 reference statements)
0
15
1
Order By: Relevance
“…Other authors [ 24 ] found that information about public health increased openness to SB, whereas in this study the message was intended to appeal to individual health benefits. Various nutrients and health-promoting compounds have been identified in SB (see [ 10 ] for a review), and health-benefit claims have shown to be effective in increasing purchase intent for specific foods containing SB [ 17 , 25 ]. However, the magnitude of the effect may depend on overall product acceptability [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other authors [ 24 ] found that information about public health increased openness to SB, whereas in this study the message was intended to appeal to individual health benefits. Various nutrients and health-promoting compounds have been identified in SB (see [ 10 ] for a review), and health-benefit claims have shown to be effective in increasing purchase intent for specific foods containing SB [ 17 , 25 ]. However, the magnitude of the effect may depend on overall product acceptability [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared to Black/African American consumers, estimated odds of a “yes” response were more than twice as high for White (OR = 2.4 for GWTTS) and up to four times higher for Hispanic/Latin/Spanish origin consumers (OR=4.1 for GWTTSH; Table 2 ) during the period of this study. In previous research [ 17 ], combined messages about safety and health benefits of catfish byproduct had a greater impact on Hispanic/Latin Americans than US Americans. In the present study, self-reported race added resolution to statistical models, and evidenced that racial identity (or associated factors) can play a part in adoption of new foods such as SB, along with other individual factors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although all hedonic scores showed a significant positive correlation (based on both Pearson's and Spearman's correlational analysis; all p ‐values <0.05) with overall WTB scores, only flavor (Pearson's r and Spearman's ρ = 0.77) and OA (Pearson's r = 0.65, Spearman's ρ = 0.64) demonstrated moderate‐to‐strong (Akolu, 2018) relationships with WTB for the optimum bread. These results are typical, as flavor is a consistent driver of food choice (Murillo et al., 2022). Average WTB scores were near the center of the 9‐point scale (4.7 for optimum bread and 4.6 for control bread; Table 4) and did not significantly differ between samples ( p ‐value = 0.57; Table 4).…”
Section: Resultsmentioning
confidence: 61%